2020
DOI: 10.1029/2019jb018910
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Postrift Lower Crustal Flow in the Northern Margin of the South China Sea

Abstract: Postrift subsidence of sedimentary basins in the northern margin of the South China Sea exceeds more than 2,.000 m, which points toward anomalous postrift crustal deformation. Previous studies have proposed lower crustal flow to explain this observation; however, this hypothesis has never been confirmed quantitatively. Here, we calculate the initial crustal structure and thermal lithospheric thickness of the northern margin of the South China Sea on the basis of recently measured heat flow data, tectonic subsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…When assessing the symmetry of the SCS margins, the pre-rifting crustal thickness, crustal rheology and structures should be taken into consideration. End-member modeling indicates that the pre-rifting crustal thickness cannot vary dramatically in the east-west direction (Hayes and Nissen, 2005), which is further confirmed by a recent study (Dong et al, 2020). Subduction of the Izanagi plate under the South China Block induced magma upwelling, which heated the lithosphere and thereby reduced the crustal viscosity (Clift et al, 2002;Brune et al, 2017).…”
Section: Symmetry Evolution In a Geodynamic Contextsupporting
confidence: 75%
See 1 more Smart Citation
“…When assessing the symmetry of the SCS margins, the pre-rifting crustal thickness, crustal rheology and structures should be taken into consideration. End-member modeling indicates that the pre-rifting crustal thickness cannot vary dramatically in the east-west direction (Hayes and Nissen, 2005), which is further confirmed by a recent study (Dong et al, 2020). Subduction of the Izanagi plate under the South China Block induced magma upwelling, which heated the lithosphere and thereby reduced the crustal viscosity (Clift et al, 2002;Brune et al, 2017).…”
Section: Symmetry Evolution In a Geodynamic Contextsupporting
confidence: 75%
“…Subduction of the Izanagi plate under the South China Block induced magma upwelling, which heated the lithosphere and thereby reduced the crustal viscosity (Clift et al, 2002;Brune et al, 2017). The pre-rift lithospheric thermal structure behavior along the east-west direction was similar to that of the pre-rifting crustal thickness (Dong et al, 2020). A series of Mesozoic NE-trending sinistral faults has been described on the South China Block (Gilder et al, 1996).…”
Section: Symmetry Evolution In a Geodynamic Contextmentioning
confidence: 86%
“…Multiple studies suggested thickness of pre‐rift brittle crust ranges from 9.14 to 12 km (Chen, 2014; Dong et al., 2020; Zhang et al., 2008). A comparison between Z uc and the suggested thickness of 12 km provides further evidence of pre‐rift inheritance of the basement crust.…”
Section: Methodsmentioning
confidence: 99%
“…The initial crustal thickness of the Cenozoic NSCS had been determined by multiple studies: 30 km based on the crustal thickness of the South China block (Zhou et al., 2012), 30–35 km based on seismic refraction modeling (Hu et al., 2009; Li et al., 2006; Nissen et al., 1995), 33 km in the eastern NSCS while 30.5 km in the western NSCS based on thermal‐subsidence modeling (Dong et al., 2020). The episodic Cenozoic rifting formed an uneven thickness of continental crust wedging oceanwards across the NSCS.…”
Section: Geological and Tectonic Settingmentioning
confidence: 99%
See 1 more Smart Citation